Medial Cuneiform Opening Wedge Osteotomy for Correction of Flexible Flatfoot Deformity: Trabecular Titanium vs. Bone Allograft Wedges. (31st March 2019) - Romeo, Giovanni; Bianchi, Alberto; Cerbone, Vincenzo; Parrini, Matteo Maria; Malerba, Francesco; Martinelli, Nicolò
Abstract : Adult flatfoot is a common pathology characterized by multiplanar deformity involving hindfoot, midfoot, and forefoot. Various surgical techniques have been described for the treatment but may not adequately correct the fixed forefoot varus component. Residual forefoot supination can be addressed by a plantar flexing opening wedge osteotomy of the medial cuneiform, also known as a Cotton osteotomy. Thus, the aims of this study were to compare clinical, radiological, and functional outcome after Cotton osteotomy, in patients treated with bone allograft or metallic implant. Consequently, 36 patients treated with opening wedge osteotomy of the medial cuneiform for forefoot varus were studied retrospectively. Patients were divided into two groups: the bone allograft group (HBG) (n=18) and the metallic implant group with BIOFOAM® Cotton Wedges (TTW) (n=18). Radiographic assessment and clinical scores including American Orthopaedic Foot and Ankle Society score, Foot Function Index, and visual analogue scale for pain were collected before operation and the last follow-up. The difference between baseline and follow-up for both groups was statistically significant for all the clinical scores and radiographic angles (p < 0.05). Most participants (92%) were very satisfied after surgery. Our results showed that Cotton osteotomy with a metallic implant provided both good clinical and radiographic outcomes comparable with bone allograft.